G595(P) Real-life clinical effectiveness of cidofovir in treating systemic paediatric adenovirus infections. (25th October 2020) - Devanahallinagaraj, C; Kapoor, S; Tang, J; Price, A; Bubb, J; Bandi, S; Joshi, M
Abstract : Aim: To report the clinical effectiveness of cidofovir in real-life paediatric patients with systemic adenovirus (AdV) infections and identify the AdV serotypes in these patients. Method: Retrospective data extracted from clinical records in a tertiary UK paediatric hospital. Results: Three children admitted to Paediatric Intensive Care Unit (PICU) with systemic AdV infection were identified between January 2017 and August 2019. Case 1: 8-year old girl with a background of developmental delay secondary to birth-related HIE (hypoxic brain injury). She had normal immunoglobulins, lymphocyte subsets and vaccination responses excluding immunodeficiency. She presented with an acute lower respiratory tract infection (LRTI) and had AdV detected in her blood, nasopharyngeal aspirate (NPA) and urine. Her blood AdV viral loads were 1.22 million copies/ml which dropped to 281 copies/ml after 3 doses cidofovir over 11 days. Case 2: 14-year old girl with a background of immunodeficiency and non –cystic fibrosis bronchiectasis, known to Immunology team presented with LRTI. At the time of the AdV (serotype 7) infection, she had a genetically undefined combined immunodeficiency. Her initial AdV loads were 16.4 million copies/ml (blood) which dropped to 145 copies/ml after 3 doses of cidofovir over 14 days. Case 3: 23-month old healthy boy presented with respiratory symptoms but deteriorated rapidly and was transferred to PICU on high frequency ventilation, but eventually required ECMO support (extra-corporeal membrane oxygenation). Despite extensive immunological investigations, no specific immunodeficiency was identified. His NPA was positive for AdV (serotype 7) and his blood AdV level was 34 million copies/ml. His AdV blood levels dropped rapidly to 50 copies/ml after 3 doses of cidofovir over the next 18 days along with intravenous immunoglobulin. Conclusion: AdV serotype 7 was identified in two of the three cases reported. Cidofovir treatment in our case series showed reduction in viral load and recovery. We noted no significant renal or hepatic impairment associated with cidofovir in any of the three cases. This case series highlights the use of cidofovir in paediatric population outside haemopoietic stem cell transplant and solid organ transplant recipients.